2017
DOI: 10.3390/rs9030302
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of GPM and TRMM Multi-Satellite Precipitation Products in Streamflow Simulations in a Data-Sparse Mountainous Watershed in Myanmar

Abstract: Satellite precipitation products from the Global Precipitation Measurement (GPM) mission and its predecessor the Tropical Rainfall Measuring Mission (TRMM) are a critical data source for hydrological applications in ungauged basins. This study conducted an initial and early evaluation of the performance of the Integrated Multi-satellite Retrievals for GPM (IMERG) final run and the TRMM Multi-satellite Precipitation Analysis 3B42V7 precipitation products, and their feasibility in streamflow simulations in the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
89
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 48 publications
8
89
3
Order By: Relevance
“…Jiang et al [19] analyzed the TRMM 3B42 product across a large region of China and obtained higher correlation coefficients in the wet part of the study area, whereas lower r values occurred mostly in relatively dry regions. Although the rainfall over the study area was better estimated in this work than in the studies by Ouatiki et al [41] and Yuan et al [20], the TRMM and Hydroe products showed high error values. Comparing satellite pixels with data from rain gauge stations involves a mismatched spatial scale because the satellite products are extracted from an area of approximately 625 km 2 for the TRMM products and of 25 km 2 for the Hydroe products, unlike the rain gauges that provide punctual rainfall measurements.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…Jiang et al [19] analyzed the TRMM 3B42 product across a large region of China and obtained higher correlation coefficients in the wet part of the study area, whereas lower r values occurred mostly in relatively dry regions. Although the rainfall over the study area was better estimated in this work than in the studies by Ouatiki et al [41] and Yuan et al [20], the TRMM and Hydroe products showed high error values. Comparing satellite pixels with data from rain gauge stations involves a mismatched spatial scale because the satellite products are extracted from an area of approximately 625 km 2 for the TRMM products and of 25 km 2 for the Hydroe products, unlike the rain gauges that provide punctual rainfall measurements.…”
Section: Discussioncontrasting
confidence: 46%
“…In this work, we used the POD to assess the ability of satellite products to estimate heavy rainfall events (rainfall > 11.57 mm day −1 ). Ouatiki et al [41] and Yuan et al [20] applied the POD to detect rainfall events (rainfall > 0.5 mm day −1 ) and found lower values than those reported here with the 3B42 product (POD = 0.7). The POD value with the Hydroe product (POD = 0.43) was similar to the values found by Ouatiki et al [41] and higher than that reported by Yuan et al [20].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…During the past years, hydrologists and meteorologists have widely evaluated and applied the TMPA products [17,18,[20][21][22][23][24][25][26]. While, the utility of the latest version 7 TMPA products in capturing extreme precipitation and streamflow has not been fully evaluated at river basin scale.…”
Section: Satellite Precipitation Productsmentioning
confidence: 99%